2015
DOI: 10.1093/nar/gkv277
|View full text |Cite
|
Sign up to set email alerts
|

Inosine modifications in human tRNAs are incorporated at the precursor tRNA level

Abstract: Transfer RNAs (tRNAs) are key adaptor molecules of the genetic code that are heavily modified post-transcriptionally. Inosine at the first residue of the anticodon (position 34; I34) is an essential widespread tRNA modification that has been poorly studied thus far. The modification in eukaryotes results from a deamination reaction of adenine that is catalyzed by the heterodimeric enzyme adenosine deaminase acting on tRNA (hetADAT), composed of two subunits: ADAT2 and ADAT3. Using high-throughput small RNA seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
122
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(134 citation statements)
references
References 48 publications
12
122
0
Order By: Relevance
“…The major drawback of RNAseq is that it often results in the detection of partially modified precursor tRNAs, rather than fully mature tRNAs 19,27 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The major drawback of RNAseq is that it often results in the detection of partially modified precursor tRNAs, rather than fully mature tRNAs 19,27 .…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with at least one of the aforementioned modifications inducing a detectable 'mutation' on the PCR amplicon. Of note, m 1 I37 has been reported to induce such a mutation as detected by RNAseq 15,19 . To show the robustness of the method using in vivo tRNA samples, we performed three independent replicates for this experiment ( Figure 7B).…”
Section: Validation Of the Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…This method presents several biases: ligation of adaptors is not equally efficient on all molecules, modifications cannot be detected, the fact of being a method based on RT-PCR means that just a few molecules can be fully sequenced. Nevertheless, several groups have used RNA sequencing datasets to detect modified tRNA residues, exploiting the fact that not all sequencing errors are technical artifacts, but, conversely, they often conceal biological marks of post-transcriptional RNA modifications sites (Ebhardt et al 2009;Iida et al 2009;Findeiss et al 2011;Ryvkin et al 2013;Torres et al 2015). By analyzing mismatches between sequencing reads and the genomic region where those reads mapped, as well as by analyzing special read patterns, they have been able to distinguish known and potentially novel post-transcriptional base modifications on tRNAs and, in some cases, also allowing a Brelative^quantification of tRNA species (Torres et al 2015).…”
Section: The State Of the Trna Population In The Cellmentioning
confidence: 99%
“…Based on the widespread differences between the RNA and DNA sequences, standard RNA-seq experiments have been used to identify numerous instances of A-to-I editing [107], and revealed that inosine is incorporated both at the pre-tRNA and mature tRNA level [108]. While this bioinformatics approach is extremely powerful, great care must be taken in the downstream analysis to discriminate true modifications from potential false positives [109].…”
Section: Overcoming the Hurdles: Towards Quantitative Profiling Of Trmentioning
confidence: 99%